Remote Inflammatory Preconditioning Alleviates Lipopolysaccharide-Induced Acute Lung Injury via Inhibition of Intrinsic Apoptosis in Rats - Yong Liu; Jiahang Xu; Liang Zhao; Jing Cheng; Baojun Chen (Journal of Immunology Research)
Background. Acute lung injury (ALI) always leads to severe inflammation. As inflammation and oxidative stress are the common pathological basis of endotoxin-induced inflammatory injury and ischemic reperfusion injury (IRI), we speculate that remote ischemic preconditioning (RIPC) can be protective for ALI when used as remote inflammatory preconditioning (RInPC). Method. A total of 21 Sprague-Dawley rats were used for the animal experiments. Eighteen rats were equally and randomly divided into the control (NS injection), LPS (LPS injection), and RInPC groups. The RInPC was performed prior to the LPS injection via tourniquet blockage of blood flow to the right hind limb and adopted three cycles of 5 min tying followed by 5 min untying. Animals were sacrificed 24 hours later. There were 2 rats in the LPS group and 1 in the RInPC group who died before the end of the experiment. Supplementary experiments in the LPS and RInPC groups were conducted to ensure that 6 animals in each group reached the end of the experiment. Results. In the present study, we demonstrated that the RInPC significantly attenuated the LPS-induced ALI in rats. Apoptotic cells were reduced significantly by the RInPC, with the simultaneous improvement of apoptosis-related proteins. Reduction of MPO and MDA and increasing of SOD activity were found significantly improved by the RInPC. Increasing of TNF-α, IL-1β, and IL-6 induced by the LPS was inhibited, while IL-10 was significantly increased by RInPC, compared to the LPS group. Conclusion. RInPC could inhibit inflammation and attenuate oxidative stress, thereby reducing intrinsic apoptosis and providing lung protection in the LPS-induced ALI in rats.